2002
DOI: 10.1787/778845424272
|View full text |Cite
|
Sign up to set email alerts
|

Investment in Human Capital Through Post-Compulsory Education and Training

Abstract: JT00129531 Document complet disponible sur OLIS dans son format d'origine Complete document available on OLIS in its original format ECO/WKP(2002)19 Unclassified English text only ECO/WKP(2002)19 2 ABSTRACT/RÉSUMÉ Investment in human capital through post-compulsory education and trainingThis paper examines various efficiency and equity aspects related to the skill acquisition of young people and older adults. The analysis suggests that such human capital investment is associated with significant labour-market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In the case of boys, whether both parents had stayed in education was significant, whereas, in the case of girls, the finding related to the mother (p. 132). A similar finding was revealed by Blondal, Field and Girouard (2002) in a report for the OECD (Figure 10, p. 44), although the paper by Webber and Thomas reveals more complexity than is initially apparent.…”
Section: Ethnicity Gender Identity and Access To Post-16 Educationsupporting
confidence: 79%
“…In the case of boys, whether both parents had stayed in education was significant, whereas, in the case of girls, the finding related to the mother (p. 132). A similar finding was revealed by Blondal, Field and Girouard (2002) in a report for the OECD (Figure 10, p. 44), although the paper by Webber and Thomas reveals more complexity than is initially apparent.…”
Section: Ethnicity Gender Identity and Access To Post-16 Educationsupporting
confidence: 79%
“…The application of this model for calculating the rate of return on investment is assumed that the age-income profiles at a given time also reflect how an individual may expect to earn income over his or her lifetime (Psacharopoulos, 1981(Psacharopoulos, , 1995Psacharopoulos & Ng, 1992;Maani, 1999;Stark, 2007). This method was applied by (Constantatos, & West, 1991;Dickson et al, 1996;Boothby & Rowe, 2002;Blondall et al, 2002;Collins & Davies, 2005;Wahrenburg & Weldi, 2007;Kara, 2009;Heckman et al, 2008;García-Suaza et al, 2009;Harberger & Guillermo-Peon, 2012) and others who were evaluating the return to investment in human capital (education) in their studies.…”
Section: The Modelmentioning
confidence: 99%
“…Studies have argued employees must be involved in all plans in order to boost performance of the learning institution because their knowledge and skills are vital for social development (Sadlak, 2000). In the era of globalisation, economic competitiveness often depends on the extent to which a country can participate in improving its university performance which will be reflected in its producing quality graduates for the nation (Blondal et al, 2002). Budhwar et al (2019) in their review on HRM studies in the Middle East concluded that majority of these studies are focused on western states (Saridakis and Cooper, 2017;Jashari and Kutllovci, 2020;Aguta and Balcioglu, 2015;Della Torre, 2019) with fewer studies on their Asian counterparts.…”
Section: Introductionmentioning
confidence: 99%